Development of energy saving conservation for educational institution - Annuar Baharuddin; Izwah Ismail (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2020)
Nowadays, electricity is the most important source of energy for each home or workplace. Consequently, an action should be planned and taken to take advantage of the benefit by using electrical energy prudently. To achieve this, the use of energy-saving equipment become crucial as they will also reserve the cost as well as providing comfort to our daily lives. This study focuses on electric energy conservation with the use of energy efficient tools (ESD), LED in the office building. The aim of this study is to identify the effects of LED lighting in the building which is available using the fluorescent light from the type of T8 36w lamps. The design of experiments using two types of headlights are T8 36W and two types of Light Emitting Diode (LED) lamps as samples. Current Data (I), Voltage (V) and Power (W) are recorded to evaluate the power difference used by both lamps. Random lighting measurements near lights are recorded using Digital Lux meters. The findings from this study showed that the use of LED lamps was more economical in terms of cost, power consumption and better lighting to its environment. It is also recommended to take the initiative to convert the existing T8 36W to LED lamps at all locations in the campus buildings to reduce the power of the electric energy (kWh) therefore the energy will be conserved as well as saving the cost of electricity usage.